Change in circulating klotho in response to weight loss, with and without exercise, in adults with overweight or obesity - Collins, Katherine A.; Ambrosio, Fabrisia; Rogers, Renee J.; Lang, Wei; Schelbert, Eric B.; Davis, Kelliann K.; Jakicic, John M. (Frontiers in Aging, 2023)
Introduction: Klotho is a protein associated with protection from aging-related diseases and health conditions. Obesity is associated with lower Klotho concentrations. Thus, this secondary analysis of adults with obesity examined 1) the change in serum Klotho concentration in response to a behavioral weight loss intervention by the magnitude of weight loss achieved; and 2) the association among serum Klotho concentration and weight, body composition, and cardiorespiratory fitness. Methods: Participants were randomized to either diet alone (DIET), diet plus 150 minutes of physical activity per week (DIET+PA150), or diet plus 250 minutes of physical activity per week (DIET+PA250). Participants (n=152; age: 45.0 + 7.9 years; body mass index [BMI]: 32.4 + 3.8 kg/m 2 ) included in this secondary analysis provided blood samples at baseline, 6-, and 12 months, and were classified by weight loss response (Responder: achieved >10% weight loss at 6 or 12 months; Non-responder: achieved <5% weight loss at both 6 and 12 months). Serum Klotho was measured using a solid-phase sandwich enzyme-linked immunosorbent assay (ELISA). Analyses of covariance (ANCOVA's) were used to examine changes in weight, body composition, cardiorespiratory fitness, and Klotho concentration by weight loss response across the 12-month weight loss intervention. Results: Responders had a greater reduction in measures of weight and body composition, and a greater increase in cardiorespiratory fitness, compared to Non-Responders (p<0.05). Change in Klotho concentration differed between Responders and Non-Responders (p<0.05), with the increase in Klotho concentration from baseline to 6 months for Responders being statistically significant. The 6-month change in Klotho concentration was inversely associated with the 6-month change in weight (rs=-0.195), BMI (rs=-0.196), fat mass (rs=-0.184), and waist circumference (rs=-0.218) (p-values <0.05).Conclusions. Findings provide evidence within the context of a behavioral intervention, with and without exercise, that change in Klotho concentration is significantly different between adults with weight loss >10% compared to <5% across 12 months. These findings suggest that weight loss and reduction in fat mass may be favorably associated with the change in Klotho concentration. This may reduce the risk of negative health consequences associated with accelerated aging in middle-aged adults.